Assessment of indicators of medical and biological monitoring of iodine deficiency diseases - L. A. Suplotova; O. B. Makarova; L. S. Kovalzhina; G. V. Sharuho (Бюллетень сибирской медицины)
The problem of iodine deficiency remains relevant all over the world due to the widespread prevalence and the negative impact it has on human health in all agegroups. Iodine deficiency leads to a decrease in the intellectual potential of children, the development of reproductive disorders at a young age, as well as the formation of multinodular toxic goiter as the last stage of goiter transformation, accompanied by heart rhythm disturbances in middle and old age. The article covers the issues of monitoring iodine deficiency in the regions of Russia and provides data on the situation in the world on the development of future prevention programs and current prevention programs. A detailed analysis of each criterion for the severity of iodine deficiency and the effectiveness of preventive programs was carried out. Particular attention is paid to the criterion of neonatal hyperthyrotropinemia as a promising indicator for monitoring iodine deficiency.